Structural Change and Economic Growth in Schengen Region - Mahmood, Tahir; Linden, Mikael (International Journal of Economics and Financial Issues, 2017)
The structural change of economy entails that in the long run how the dynamics of three main sectors (i.e. agriculture, industry and services) are related to economic growth. We conduct Granger non-causality (GC) tests with data from 15 Schengen countries in period 1970-2012. The results confirmed that industry sector is still the “engine” of economy and the larger service sector retards the gross domestic product per capita (GDPc) growth rate in Schengen region. The results support Baumol's argument concerning the productivity differences and their growth effects across the sectors. Keywords: Sector shares, economic growth, panel data, co-integration, error correction JEL Classifications: E1, E2, J, O1, O4